Sparkle through Speech 1.0: My Courageous Voice & Growth Mindset / Marni Jamil - Jamil, Marni (Academy of Language Studies, 2024)
The Sparkle through Speech 1.0: My Courageous Voice & Growth Mindset programme (STS 1.0) was organised by Ms. Marni Jamil, a lecturer from the Academy of Language Studies (APB), Universiti Teknologi MARA Pulau Pinang Branch (UiTMCPP). As an alumna of UiTM, this contribution shows a commitment to give back to the prestigious institution that plays a pivotal role in shaping academic and personal development. The programme was held on 28 August 2023 and conducted in the Seminar Room of the Islamic Centre, UiTMCPP. The implementation of this ambitious program was facilitated by the collaborative support of the UiTMCPP management, APB lecturers, the Islamic Centre, He & She Coffee, and Mardelish. The diverse contributions from individuals in various capacities played a crucial role in ensuring the success of STS 1.0.